MODEL PENDEKATAN PROSES DALAM PEMBELAJARAN MENULIS (ECRIRE) WACANA NARATIF PADA MAHASISWA SEMESTER III JURUSAN PENDIDIKAN BAHASA DAN SASTRA ASING PROGRAM STUDI PENDIDIKAN BAHASA PRANCIS (Lingua, 2009)
This research focused on the Proces-Approach Model in Narrative DiscourseWriting Learning. The four research questions: (1) how are the third semesterstudents’ perception in Language and Litterature Foreign Departement,French Education Study Programme on Proces Approach Model in NarrativeDiscourse of Writing Learning before a treatment, (2) how and how manypercents their capability of Narrative Discourse Writing are before a treatment,(3) how and how many percents their capability of Narrative Discourse Writingare after a treatment, and (4) how are the third semestre students’ perceptionin Language and Litterature Foreign Departement, French Education StudyProgramme on Proces Approach Model in Narrative Discourse of WritingLearning after the treatment? The perception data was taken by questionnairewhich was done 2 x, before and after the treatment, whereas thestudents’capability to write a narrative discourse was used by pretest andposttest. The findings show that firstly, the pretest result is various. Thestudents’s kwnoledge of definition narrative discourse reach 80 %, of narrativediscourse organition 92 %, of the experience writing of narrative discourse76%, and of the writing step 72 %. Besides, the students’ unknown of lexicaland grammatical marquers reach 80 % and 88 %. Secondly, totally, if I comparethe first and the second test, the result shows that the students who got A, B,and D decrease, from 1 to 0 student (5,26%), from 8 to 7 students (5,26%), andfrom 3 to 1 student (10,53%). But the students who got C and D increase, from5 to 8 students (15,79%) and from 2 to 3 students (5,26%). Finally, thestudents’ perception after the treatment indicate a various result. 80 %students are not satisfied of theirs narrative discourse writings, 60 % studentsstill has some difficulties, 80 % students are conscious of theirs weakness, and84 % students agreed about the researcher’s evaluation.Keywords: capability, writing, narrative discourse, proces approach writing model